Pick a Number : the U.S. and International Accounting. - Hussey, Roger (Financial accounting and auditing collection., 2018)
This second edition describes the successes and failures of the convergence project. The U.S. involvement brought about many changes in corporate financial reporting, but there were differences in opinions on specific issues. This resulted in the FASB, US focusing on its own regulations. We explain the main convergence achievements and also the differences leading to the end of the project. Our analysis reviews new developments in corporate reporting, including the issues of sustainability, governance, and integrated reporting.